COMPARATIVE ANALYSIS OF TOOTH MOVEMENT BIOMECHANICS USING ALIGNERS AND BRACKET SYSTEMS IN THE TREATMENT OF DISTAL OCCLUSION - Usmonova Zamira Akramovna; Kamalova Mehriniso Kilichevna (Modern American Journals, 2025)
This study presents a comparative investigation of biomechanical protocols applied in the orthodontic correction of distal occlusion using clear aligners and conventional fixed appliances. Clinical outcomes derived from the analysis of 483 cases demonstrate statistically significant differences in treatment duration, force application strategies, and anchorage management between the two systems. Bracket-based mechanics rely on continuous archwire-induced forces and reciprocal anchorage, permitting complex three-dimensional movements including root torque, controlled tipping, and space closure with extraction protocols. Aligners employ segmented, digitally staged displacement via localized pressure points and optimized attachments, allowing for targeted movements with reduced biological strain. However, limitations in root parallelism, extrusion control, and molar distalization capacity are evident in aligner therapy without auxiliary aids. Despite these constraints, aligners yield effective results in selected Class II malocclusion cases, particularly under conditions of high patient compliance and digitally guided treatment staging. The findings underscore the necessity of case-specific biomechanical planning when selecting between aligner and bracket-based approaches for distal occlusion management.
Keywords: Distal occlusion; clear aligners; fixed appliances; orthodontic biomechanics; torque control; staged displacement; reciprocal anchorage; treatment duration; root parallelism; extrusion mechanics; digital orthodontic planning; force vectors.